Innovation of Brand Building and Character Development in Islamic School: A Transformation Based on School Core Values - Cahyanto, Bagus; Wibowo, Agus Mukti; Arifuddin, Ahmad; Dewi, Damajanti Kusuma; Salamah, Evi Rizqi; Don, Abdul Ghafar (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This paper describes the innovation process of Islamic schools in building students' image and character. This research was conducted at the primary education level, specifically at a private junior high school in the suburbs. The school has proven successful in building its image and character education model, transforming it from a public school into a leading school chosen by parents. Furthermore, this school was selected based on several other factors, including its unique history and its position as a leading and exemplary Islamic school in Malang, Indonesia. This study employs a qualitative case study approach, with data collection conducted through interviews, observations, and documentation. In the data analysis process, the researcher used case study data analysis, as described by Yin, which consists of four parts: pattern matching, explanation building, time series analysis, and repeated observations. The study's results revealed that the school was initially an underappreciated Islamic school with lower parental school preferences. The school did not offer any specialisations or achievements to prospective students. After the school innovated by initiating and articulating its core values in various aspects of the school, including the curriculum, environment, and social media, the school's core values became a driving force in developing character education and enhancing the school's brand. This condition attracts public attention and increases parental preference for schools. This study suggests that initiating and articulating unique and strong core values is a breakthrough that can transform the brand and character education model of schools, ultimately increasing parental preference for these institutions. This study recommends further quantitative research to measure the specific impact of implementing core values ​​on parental preferences in a more measurable manner.